Impact Analysis and Selection of Spray Drying Parameters for Dawn and Feather Protein Hydrolysates - Piskaeva A.; Babich O.; Yang Y. (Техника и технология пищевых производств)
Down and feather waste represents a promising source of feed protein. The main component of feather is protein, predominantly β-keratine. Keratin is a mechanically durable and chemically unreactive protein with cistein, glutamine, and protein as dominating amino acids in its structure. According to the chemical composition (amino acid content, balance of micro-and macronutrients), the feather raw material is a valuable source of nutrients as a component of feed additives. The aim of this work was to analyze the efficiency and selection of parameters of spray drying of hydrolysate of feather and down waste products. Dry feed additives obtained by spray drying have a lot of advantages, such as dosing accuracy, compactness, storage time, and a possibility of targeted use in dissolved form. In addition, they are easy to package and transport. The most important quality indicators of feed additives include the mass fraction of moisture and the yield of the finished product. The main parameters of spray drying that affect the mass fraction of moisture and the yield of the final product are the drying temperature, aspiration (air flow rate), and the rate of solution feeding to the installation. According to the experiment conducted, the spray drying temperature of 70.0 ± 5.0°C caused no loss of essential amino acids. In addition, no undesirable substances were formed, unlike in other technologies that use hightemperature treatment (90–120 ± 5.0°C) and hydrolysis, which reduces the biological value of the feed product. This temperature was found optimal for keratin hydrolysates during drying. The optimal value of the parameter of the solution flow rate was 6.5 ± 0.5 ml/min. The optimal range of air flow rates during spray drying of hydrolysates of feather raw materials was 20.0 ± 5.0 m3/h. This temperature provides the maximum yield of the finished product and the minimum mass fraction of moisture.